Performance evaluation of the GastroPlusTM software tool for prediction of the toxicokinetic parameters of chemicals. Issue 11 (2nd November 2018) - Zhang, F.; Bartels, M.; Clark, A.; Erskine, T.; Auernhammer, T.; Bhhatarai, B.; Wilson, D.; Marty, S.
ABSTRACT: The accurate prediction of toxicokinetic parameters arising from oral, dermal and inhalation routes of chemical exposure is a key element in chemical safety assessments. In this research, the physiologically based pharmacokinetic (PBPK) GastroPlus TM software was evaluated against a series of chemicals for the prediction of toxicokinetic parameters. Overall,  67% of predicted intrinsic clearance (Clint) values were within 1- to 10-fold of empirical data for 463 compounds, and 87% of the predicted fraction unbounded in plasma (Fup) values were 1- to 3-fold of empirical data for 441 compounds. The r 2 (coefficient of determination) of predicted Cmax (maximum plasma concentration) and AUC (Area Under Curve) values versus the corresponding empirical values from oral, inhalation and dermal exposures ranged from 0.04 to 0.92. Among the three exposures, the highest r 2 values, ranging from 0.80 to 0.92, were observed for oral exposure predictions, where 88% of the compounds had 1- to 10-fold differences between predicted and empirical values for Cmax and AUC. The predicted plasma Css (steady-state plasma concentration) values were consistent with those Css values calculated by in vitro-to-in vivo extrapolation (IVIVE) approaches using experimental parameters. Based on the evaluation results, GastroPlus™ can be used as a QSAR/PBPK tool for toxicokinetic parameter predictions.